1976
DOI: 10.1152/jn.1976.39.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Depolarizing afterpotentials and burst production in molluscan pacemaker neurons

Abstract: 1. Spikes in molluscan bursting cells are followed by depolarizing afterpotentials (DAPs) which are not seen in nonbursting cells in the same ganglia. DAPs from successive spikes sum to provide a depolarizing drive capable of sustaining multiple discharge. 2. Subthreshold depolarization activates a DAP-like process in bursters. 3. DAP amplitude increases as the cell is hyperpolarized beyond the potassium equilibrium potential. The amplitude is not changed by intracellular iontophoresis of TEA-Cl. DAP amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
47
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 0 publications
6
47
0
Order By: Relevance
“…The DAPs last for hundreds of milliseconds to seconds and have amplitudes up to 10 mV, depending on the number of preceding spikes and membrane potential levels at which they are evoked (Andrew & Dudek, 1984;Andrew, 1987). Resembling those identified in invertebrate bursting pacemaker neurones (Thompson & Smith, 1976;Kramer & Zucker, 1985a) and other mammalian CNS neurones (Llin as, 1988;White, Lovinger & Weight, 1989), DAPs as well as phasic firing in SON neurones are abolished by depleting extracellular Ca¥, blocking membrane Ca¥ channels or chelating cytosolic free Ca¥ (Inenaga, Akamatsu, Nagatomo, Ueta & Yamashita, 1992;Li et al 1995). Our recent study has further demonstrated that interference with Ca¥-induced Ca¥ release from internal stores, with either blockade of intracellular ryanodine receptors or depletion of internal Ca¥ pools, reduces DAPs and eliminates phasic firing in SON cells (Li & Hatton, 1997).…”
supporting
confidence: 52%
“…The DAPs last for hundreds of milliseconds to seconds and have amplitudes up to 10 mV, depending on the number of preceding spikes and membrane potential levels at which they are evoked (Andrew & Dudek, 1984;Andrew, 1987). Resembling those identified in invertebrate bursting pacemaker neurones (Thompson & Smith, 1976;Kramer & Zucker, 1985a) and other mammalian CNS neurones (Llin as, 1988;White, Lovinger & Weight, 1989), DAPs as well as phasic firing in SON neurones are abolished by depleting extracellular Ca¥, blocking membrane Ca¥ channels or chelating cytosolic free Ca¥ (Inenaga, Akamatsu, Nagatomo, Ueta & Yamashita, 1992;Li et al 1995). Our recent study has further demonstrated that interference with Ca¥-induced Ca¥ release from internal stores, with either blockade of intracellular ryanodine receptors or depletion of internal Ca¥ pools, reduces DAPs and eliminates phasic firing in SON cells (Li & Hatton, 1997).…”
supporting
confidence: 52%
“…are reduced when Na+ or Ca2+ are removed from the bathing medium (Thompson, 1976). It has also been suggested that d.a.p.s provide a mechanism for sustaining repetitive firing, and are critical for the depolarizing phase of bursting pace-maker activity (Thompson & Smith, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…DAP sizes depend on the number of preceding spikes and can be reduced by membrane hyperpolarization (Andrew & Dudek, 1984a;Andrew, 1987). Removal of extracellular Ca2+, blockade of membrane Ca2+ channels or chelation of intracellular free Ca2+ all abolish DAPs , suggesting that DAPs in SON cells, like those identified in invertebrate bursting pacemaker (Thompson & Smith, 1976;Kramer & Zucker, 1985) and mammalian (White, Lovinger & Weight, 1989) neurones require Ca2+ influx for their generation. However, ionic mechanisms underlying these potentials are not yet well understood, although DAPs in SON neurones are recognized to be important in the formation of phasic or burst firing patterns that promote vasopressin release from the neurohypophysis (see Hatton, 1990, for review).…”
mentioning
confidence: 97%